Roles and Mechanisms of DNA Methylation in Vascular Aging and Related Diseases - Xu, Hui; Li, Shuang; Liu, You-Shuo (Frontiers in Cell and Developmental Biology, 2021)
Vascular aging is a pivotal risk factor promoting vascular dysfunction, the development and progression of vascular aging-related diseases. The structure and function of endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) are disrupted during the aging process, causing ECs and VSMCs senescence as well as vascular dysfunction. DNA methylation, an epigenetic mechanism, involves the alteration of gene transcription without changing the DNA sequence. It is a dynamically reversible process modulated by methyltransferases and demethyltransferases. Emerging evidence reveals that DNA methylation is implicated in the vascular aging process and plays a central role in regulating vascular aging-related diseases. In this review, we seek to clarify the emerging mechanisms of DNA methylation in modulating ECs and VSMCs functions and primarily focus on the association of DNA methylation with vascular aging-related diseases. Therefore, we represent many vascular aging-related genes which are modulated by DNA methylation. Besides, we concentrate on the potential clinical application of DNA methylation serve as reliable diagnostic tool and effective therapeutic target for vascular aging-related diseases.